Modeling and Analysis of Quasi-3D Equivalent Magnetic Network of Direct-Drive Inner Boost Permanent Magnet Motor - Jiacheng Wu; Shuai Wang; Yan Hu; Bingyi Zhang; Xuefeng Xu (IEEE Access)
To address the problems of low space utilization and weak overload capacity of traditional dual-stator permanent magnet motors with equal-length cores, a kind of inner boost permanent magnet motor (IBPMM) with unequal-length cores is proposed. First, the topological structure and inner stator start-stop control method of the IBPMM are introduced. Then, aiming at the problem that finite element model (FEM) is difficult to analyze the variation law of the outer stator torque when the rotor yoke is saturated caused by the high inner stator current, a new quasi-3D equivalent magnetic network (EMN) model with invariable air-gap permeance and accounting for saturation and flux leakage is proposed by using superposition method. The model is used to analyze air-gap flux density, flux linkage and no-load EMF of the IBPMM under different working conditions, and further separates the inner stator torque and outer stator torque, so as to analyze the change of the outer stator torque under different high-density inner stator currents. According to the quasi-3D EMN results, the proposed IBPMM has 3 times short-term overload capacity, and the outer stator torque decreases by only approximately 0.5% at the maximum inner boost current. Finally, the performance of the proposed IBPMM and the accuracy of the quasi-3D EMN are verified by 3D FEM and prototype experiments.